1994
DOI: 10.1111/j.1600-0765.1994.tb01244.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β stimulates collagenase production by cultured human periodontal ligament fibroblasts

Abstract: To examine the effects of interleukin-1 beta (IL-1 beta) on collagenase production by human periodontal ligament fibroblasts (PLF) and gingival fibroblasts (GF) in culture, collagenase activity in conditioned media was determined using a novel procedure that circumvented interference by enzyme inhibitors. Fibroblasts obtained from five paired periodontal ligament and gingival tissues were cultured for two weeks, and then incubated for a further 72 h in alpha-MEM supplemented with various concentrations of IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…Several studies have shown that IL-1 gives rise to elevated levels of immunoreactive procollagenase as well as steady-state transcripts in both gingival fibroblasts (GF) and periodontal ligament fibroblasts (PLF) (Meikle et al, 1989;Richards and Rutherford, 1990;Lark et al, 1990;Tewari et al, 1994). PLF appear to be more sensitive to IL-1I3 than GF and exhibit a 2.4-5.2-fold increase in collagenase activity as compared with a 1.4-2.2-fold increase for GF (Ohshima et al, 1994). No significant change in inhibitor synthesis was observed after treatment of PLF and GF with IL-I13 (Meikle et al, 1989) as well as TIMP-1 mRNA level in PLF (Alvares et al, 1995).…”
Section: (G) Influence Of Il-i On Collagen Synthesismentioning
confidence: 99%
“…Several studies have shown that IL-1 gives rise to elevated levels of immunoreactive procollagenase as well as steady-state transcripts in both gingival fibroblasts (GF) and periodontal ligament fibroblasts (PLF) (Meikle et al, 1989;Richards and Rutherford, 1990;Lark et al, 1990;Tewari et al, 1994). PLF appear to be more sensitive to IL-1I3 than GF and exhibit a 2.4-5.2-fold increase in collagenase activity as compared with a 1.4-2.2-fold increase for GF (Ohshima et al, 1994). No significant change in inhibitor synthesis was observed after treatment of PLF and GF with IL-I13 (Meikle et al, 1989) as well as TIMP-1 mRNA level in PLF (Alvares et al, 1995).…”
Section: (G) Influence Of Il-i On Collagen Synthesismentioning
confidence: 99%
“…13 Several methods are known to detect collagenase products among others is collagenase activity assay with collagen as substrate which products are then separated by sodium dodecyl sulphate polyacrylamide electrophoresis (SDS-PAGE). 8,10 The purpose of this study was to evaluate the effect of Jatropha curcas latex on the release of collagenase by fibroblast cells. Materials for collagenase assay: APMA buffer: 7 mg APMA (4-aminophenyl mercuric acetate) was weighed in a glass test tube.…”
mentioning
confidence: 99%
“…9 Enzyme secretion can be induced by several agents as endotoxin, immune complex, and IL-1. 8 In periodontal disease, collagenase increase with the severity of the disease. 13 Several methods are known to detect collagenase products among others is collagenase activity assay with collagen as substrate which products are then separated by sodium dodecyl sulphate polyacrylamide electrophoresis (SDS-PAGE).…”
mentioning
confidence: 99%
See 2 more Smart Citations